Study Habits and Anxiety in Andragogic Students - Montes-Valer, Rosa Esther (2020)
The objective of this research was to determine the relationship between study habits and self-assessment of anxiety in andragogic students. The research design was non-experimental, cross-sectional of comparative type. The study population consisted of 180 students of the Administration career of the "Working Adult" program of the Private University of the North (UPN), enrolled in the first cycle of the Communication Skills course and the sample size was 139 students. For the measurement of the research variables, the anxiety self-assessment (prepared by Zung), the study Habits inventory (prepared by Luis Vicuña Peri) was used. A significant negative correlation was found between both variables, which means that the group of people who reported higher levels of anxiety had lower rates of study habits.